Pathways to purpose among impoverished youth from the Guatemala City Dump community - Belle Liang; Allison White; Haley Rhodes; Rachel Strodel; Ellen Gutowski; Angela M. DeSilva Mousseau; Terese Jean Lund (Community Psychology in Global Perspective, 2017)
Nongovernmental organizations (NGOs), such as Potter’s House Association (PHA), work to build capacity in impoverished communities surrounding the Guatemala City Garbage Dump. Specifically, PHA provides educational and mentoring interventions to help youth find purpose in overcoming poverty. In this multi-source study, in-depth interviews with Guatemalan high school graduates who have participated in the PHA education and mentoring program, and qualitative surveys with PHA staff members who have worked in this program as mentors and teachers were thematically analyzed using a grounded theory approach. Their responses were categorized into four themes associated with youth purpose: 1) people; 2) prosocial benefits; 3) passion; and 4) propensity. The data suggest that purpose development for this youth population seems especially influenced by religious faith and family values, and may be impeded by poverty, social location, and other obstacles. Findings provide insights for programs designed to change communities through youth empowerment and education.